World class cooking for solving global challenges : reparadigming societal innovation - Mercier-Laurent, E.; Edvinsson, Leif (Emerald Publishing Limited, 2021)
When faced with new global challenges propelled by social, financial, economic, health and environmental crisis, the leaders of today need alternative answers to those posed by traditional policies. In this book, Mercier-Laurent and Edvinsson consider a cutting-edge thought methodology for solving global challenges - by looking at societal innovation through the lens of an analogy to cooking. How might we apply the power of cooking to connect imagination, knowledge, know-how and pleasure to real-world problems? Envisioning an ecosystem dynamic which connects various components, and requires multiple resources with the aim of securing sustainable well-being, the authors showcase initiatives for societal innovation which involve the use of diverse talents, evolving behaviours, thinking differently, adapting to the use of technology and close attention to human purpose. Demonstrating that the possibilities of technology are underused for solving critical problems because of the continual perpetuation of the same cognitive approaches, time and time again, this book makes a crucial intervention by serving up a new perspective on obtaining a sustainable and prosperous future that traditional approaches have so far not reached. By presenting a broad range of promising experiments from around the world, the authors inspire readers to re-imagine their idea of how societal innovation might be achieved. In this book they provide the first of many new recipes for successful global change-making.